ENTERPRISE LEVEL SECURITY 1 & 2 - Foltz, Kevin E.; Simpson, William Randolph, 1946- ([Place of publication not identified] CRC Press, 2020)
This is a set, comprising of Enterprise Level Security and Enterprise Level Security 2. Enterprise Level Security: Securing Information Systems in an Uncertain World provides a modern alternative to the fortress approach to security. The new approach is more distributed and has no need for passwords or accounts. Global attacks become much more difficult, and losses are localized, should they occur. The security approach is derived from a set of tenets that form the basic security model requirements. Many of the changes in authorization within the enterprise model happen automatically. Identities and claims for access occur during each step of the computing process. Many of the techniques in this book have been piloted. These techniques have been proven to be resilient, secure, extensible, and scalable. The operational model of a distributed computer environment defense is currently being implemented on a broad scale for a particular enterprise. The first section of the book comprises seven chapters that cover basics and philosophy, including discussions on identity, attributes, access and privilege, cryptography, the cloud, and the network. These chapters contain an evolved set of principles and philosophies that were not apparent at the beginning of the project. The second section, consisting of chapters eight through twenty-two, contains technical information and details obtained by making painful mistakes and reworking processes until a workable formulation was derived. Topics covered in this section include claims-based authentication, credentials for access claims, claims creation, invoking an application, cascading authorization, federation, and content access control. This section also covers delegation, the enterprise attribute ecosystem, database access, building enterprise software, vulnerability analyses, the enterprise support desk, and network defense. Enterprise Level Security 2: Advanced Topics in an Uncertain World follows on from the authors' first book on Enterprise Level Security (ELS), which covered the basic concepts of ELS and the discoveries made during the first eight years of its development. This book follows on from this to give a discussion of advanced topics and solutions, derived from 16 years of research, pilots, and operational trials in putting an enterprise system together. The chapters cover specific advanced topics derived from painful mistakes and numerous revisions of processes. This book covers many of the topics omitted from the first book including multi-factor authentication, cloud key management, enterprise change management, entity veracity, homomorphic computing, device management, mobile ad hoc, big data, mediation, and several other topics. The ELS model of enterprise security is endorsed by the Secretary of the Air Force for Air Force computing systems and is a candidate for DoD systems under the Joint Information Environment Program. The book is intended for enterprise IT architecture developers, application developers, and IT security professionals. This is a unique approach to end-to-end security and fills a niche in the market. Dr. Kevin E. Foltz, Institute for Defense Analyses, has over a decade of experience working to improve security in information systems. He has presented and published research on different aspects of enterprise security, security modeling, and high assurance systems. He also has degrees in Mathematics, Computer Science, Electrical Engineering, and Strategic Security Studies. Dr. William R. Simpson, Institute for Defense Analyses, has over two decades of experience working to improve systems security. He has degrees in Aeronautical Engineering and Business Administration, as well as undergoing military and government training. He spent many years as an expert in aeronautics before delving into the field of electronic and system testing, and he has spent the last 20 years on IT-related themes (mostly security, including processes, damage assessments of cyber intrusions, IT security standards, IT security evaluation, and IT architecture).
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Cryptography; COMPUTERS / Groupware; Computer networks -- Security measures; Industries -- Security measures